Disentangling real space fluctuations: The diagnostics of metal-insulator transitions beyond single-particle spectral functions - Michael Meixner; Marcel Krämer; Nils Wentzell; Pietro M. Bonetti; Sabine Andergassen; Alessandro Toschi; Thomas Schäfer (Physical Review Research)
The destruction of metallicity due to the mutual Coulomb interaction of quasiparticles gives rise to fascinating phenomena of solid state physics such as the Mott metal-insulator transition and pseudogap. A key observable characterizing their occurrences is the single-particle spectral function, determined by the fermionic self-energy. In this paper, we investigate in detail how real space fluctuations are responsible for a self-energy that drives the Mott-Hubbard metal-insulator transition. To this aim, we first introduce a real space fluctuation diagnostics approach to the Hedin equation, which connects the fermion-boson coupling vertex λ to the self-energy Σ. Second, by using cellular dynamical mean-field theory calculations, we unambiguously identify nearest-neighbor antiferromagnetic excitations as the leading physical processes responsible for the destruction of metallicity across the transition.